Applying Multi-Agent Intelligent System to Decision Making with Knowledge Management Approach - Masoomeh Moradi; Abdollah Aghaie; Monireh Hosseini (Journal of Information Technology Management)
Todays, decision makers in the organization need toconstantly monitor changes in the environment and organization andmake necessary changes. Therefore knowledge about the environmentand organization is necessary in decision making. Knowledgemanagement is a key factor for competitive business environment andorganizations are investing heavily in creating centralized knowledgerepositories to improve business processes, promoting knowledge sharingand retaining expertise even after employees have left the organization.Corporations also tend to look for systems to assist them in knowledgemanagement with high speed and accuracy. One of the tools in this areahas proven to be effective and efficient, is intelligent agent. The study aimsto provide an infrastructure for knowledge management using intelligentagents in such that takes into consideration all aspects of knowledgemanagement and also to overcome the challenges and weaknesses ofother studies. Simulation of the proposed system in a car factory indicatesthat it is efficient and effective in supporting and improving decisionmaking.